Managerial Ownership Moderates the Relationship between Profitability, Corporate Social Responsibility, and Tax Planning on Company Value (A Study of Manufacturing Companies Listed on the Indonesia Stock Exchange for the Period 2021-2024) - Nur Azizah, Jihan; Zuraidah (E-Jurnal Akuntansi, 2026)
This research examines the impact of profitability, CSR, and tax planning on firm value in Indonesia Stock Exchange (IDX)-listed industrial manufacturing businesses from 2021 to 2024, using management ownership as a moderating variable. Purposive selection of 26 firms' annual reports, financial statements, and sustainability reports provided secondary data. Profitability was assessed by ROA, CSR by a GRI-based disclosure index, and tax planning by the Effective Tax Rate. Tobin's Q proxied firm value, and moderated regression analysis examined management ownership. The findings should show how management ownership moderates the link between financial and sustainability characteristics and company value. This research adds to accounting and finance literature and offers management, investors, and regulators practical advice on company transparency and sustainability.